Electrically debondable adhesive and preparation method thereof

By using acrylic polymers and modified electrode materials in electrical adhesive adhesives, combined with conductive fillers and organic silicon compounds containing amino groups, the problem of insufficient adhesive bonding strength and unstable conductive performance of existing adhesives. The effect of high adhesion intensity, good conductivity, and rapid detachment is achieved, and it is suitable for the rapid disassembly and replacement of electronic components.

CN119371916APending Publication Date: 2025-01-28ZHEJIANG BAICHUN NEW MATERIAL CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411827090.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing electrically debondable adhesives are insufficient in the initial bonding stage and are prone to bond failure under mechanical stress. The conductive properties are affected by temperature and humidity. The debonding process is slow, adapting to rapid disassembly and replacement of electronic components. Inadequate demand.

Method used

The use of acrylic polymers is used as the main ingredient, combined with conductive fillers such as carbon nanotubes and modified electrode materials, and the introduction of organic silicon compounds containing amino groups for modification, enhance the conductive performance and adhesion strength of the adhesive, and use specific specific through specific The formula and preparation method improve the flexibility and weather resistance of the adhesive.

Benefits of technology

It significantly improves the adhesive and conductive performance of adhesives, ensure good performance under various environmental conditions, achieve rapid adhesion, reduce maintenance costs and time, and apply to the assembly and maintenance of electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371916A_ABST
    Figure CN119371916A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of debondable adhesives, in particular to an electrically debondable adhesive and a preparation method thereof. The electrode material comprises an acrylate polymer, a conductive filler, a plasticizer, an antistatic agent, a curing agent, a modified electrode material and an auxiliary agent, the modified electrode material is prepared by modifying a basic electrode material through a modifier, is used for improving the electrolysis speed of the electrically debondable adhesive, and interacts with the acrylic polymer to improve the bonding performance. By introducing the modified electrode material, the adhesive can quickly respond and realize quick debonding after a specific voltage is applied; the cost and the difficulty of disassembling and replacing elements can be greatly reduced, meanwhile, damage to the elements is avoided, and the maintenance efficiency and the reliability of the electronic equipment are improved. The adhesive disclosed by the invention can still keep good adhesive performance and conductivity after being used for a long time, and the service life of a product is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of debondable adhesives, in particular to an electrically debondable adhesive and a preparation method thereof. Background Art

[0002] Compared with other methods such as temperature, UV light, and solvents, the use of electricity as an external stimulus in existing electrolytic debonding technologies has obvious advantages, such as avoiding damage to temperature-sensitive components. Electrically induced adhesive debonding technology is of great significance for the recycling, repair, and reuse of electronic devices, furniture, and automobiles. However, the complexity of adhesives makes it a major obstacle to analyze the mechanism of debonding under actual conditions.

[0003] In order to properly recycle manufactured goods, adhesives need to be redesigned to allow for the recycling of materials. Smart adhesives that can be debonded are essential for practical debonding. However, existing electrically debondable adhesives still have some shortcomings, such as:

[0004] Although existing electrically removable adhesives can be debonded after voltage is applied, their bonding strength is often not high enough in the initial bonding stage, especially in situations where they need to withstand large mechanical stress, which can easily lead to bonding failure. Secondly, in complex and changeable working environments, the conductivity of existing electrically removable adhesives is easily affected by factors such as temperature and humidity, resulting in poor conductivity. Moreover, if the debonding process is relatively slow, it will take a long time to completely debond, which is particularly inconvenient in situations where electronic components need to be quickly disassembled or replaced, increasing maintenance costs and time. Summary of the invention

[0005] The object of the present invention is to provide an electrically debondable adhesive and a preparation method thereof to solve the problems raised in the above background technology.

[0006] To achieve the above object, on the one hand, the present invention provides an electrically debondable adhesive, comprising the following raw materials:

[0007] Acrylic acid ester polymer, 50-60 parts by weight; the acrylic acid ester polymer adopts butyl acrylate-ethyl acrylate copolymer, which is an acrylic acid ester polymer with high bonding strength and good flexibility.

[0008] Conductive filler, 3-5 parts by weight; the conductive filler is at least one of carbon nanotubes, graphene and conductive polymers, and is used to improve the conductive properties of the adhesive; carbon nanotubes have high conductivity and good mechanical properties, which can significantly improve the conductive properties of the adhesive; graphene has extremely high conductivity and good thermal stability, which can enhance the conductive properties and thermal stability of the adhesive; conductive polymers have good conductivity and transparency, and are suitable for application scenarios requiring transparent adhesives.

[0009] Plasticizer, 8-12 parts by weight; the plasticizer is one of dioctyl phthalate or dioctyl sebacate. Dioctyl phthalate can effectively improve the flexibility and processing properties of the adhesive, while dioctyl sebacate has good cold resistance and heat resistance and is suitable for applications within a wide temperature range.

[0010] Antistatic agent, 2-4 parts by weight; the antistatic agent is a quaternary ammonium salt antistatic agent or a polyether antistatic agent.

[0011] Curing agent, 3-5 parts by weight; the curing agent is one of isocyanate curing agent or epoxy resin curing agent.

[0012] Modified electrode material, 5-10 parts by weight; the modified electrode material is prepared by modifying a basic electrode material with a modifier; the basic electrode material is one of silver nanowires, conductive fibers and metal foil; the modifier is an organosilicon compound containing amine groups, the amine groups can form chemical bonds with the surface of the basic electrode material, increase the surface activity of the material, and thus improve the compatibility and dispersibility between the electrode material and other components in the adhesive; at the same time, the amine groups can also interact with the hydroxyl groups in the acrylic polymer to form weak interaction forces such as hydrogen bonds, which helps to improve the overall bonding performance of the adhesive; through the combination of the amine groups and the basic electrode material, the conductivity of the basic electrode material can be improved, so that when a voltage is applied, the electrode material can respond more quickly, thereby accelerating the redistribution of the internal charge of the adhesive and promoting the occurrence of the debonding process; the organosilicon compound itself has good weather resistance and can resist the influence of factors such as ultraviolet rays and moisture, which helps to maintain the stable performance of the adhesive under different environmental conditions and ensure its long-term use effect.

[0013] The organosilicon compound containing an amine group adopts one of amino silicone oil, amino-modified silicone coupling agent (3-aminopropyltriethoxysilane) or amino-modified polysiloxane (polydimethylsiloxane-amino modified);

[0014] The chemical structure of amino silicone oil is R2SiO_n, where R can be an alkyl group such as methyl or ethyl, and an amino group is present at the end or side chain;

[0015] The amino group in 3-aminopropyltriethoxysilane can chemically adsorb with the hydroxyl group or other functional groups on the surface of the electrode material to form a stable chemical bond, thereby improving the surface activity and dispersibility of the electrode material. At the same time, 3-aminopropyltriethoxysilane can be used as a coupling agent to improve the interface bonding between the filler and the polymer and improve the overall performance of the adhesive.

[0016] The amino group in the polydimethylsiloxane-amino modified can chemically adsorb with the hydroxyl or other functional groups on the surface of the electrode material to form a stable chemical bond, thereby improving the surface activity and dispersibility of the electrode material. At the same time, the polydimethylsiloxane-amino modified has good flexibility and processing properties, which helps to improve the mechanical properties of the adhesive.

[0017] Auxiliary agents, 2-4 parts by weight; the auxiliary agents include antioxidants, ultraviolet absorbers and coupling agents.

[0018] As a further improvement of the technical solution, the conductive polymer is one of poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate, polypyrrole or polyaniline.

[0019] As a further improvement of the present technical solution, the quaternary ammonium salt antistatic agent adopts stearyl trimethyl sodium chloride, which has good antistatic performance and compatibility, and the polyether antistatic agent adopts polyoxyethylene ether, which has good antistatic performance and water solubility, and is suitable for application scenarios requiring moisture-proofing.

[0020] As a further improvement of the present technical solution, the isocyanate curing agent adopts one of toluene diisocyanate or hexamethylene diisocyanate, which can react with the hydroxyl groups in the acrylic polymer to form a cross-linked network to improve the mechanical properties and heat resistance of the adhesive; the epoxy resin curing agent adopts bisphenol A epoxy resin, which can react with the hydroxyl groups in the acrylic polymer to form a stable cross-linked structure.

[0021] As a further improvement of the present technical solution, the antioxidant adopts antioxidant 1010, which can effectively prevent the adhesive from oxidative degradation at high temperature; the ultraviolet absorber adopts UV-326, which can effectively absorb ultraviolet rays and prevent the adhesive from aging; the coupling agent adopts silane coupling agent, which can improve the interface bonding between the filler and the polymer and improve the comprehensive performance of the adhesive.

[0022] As a further improvement of the technical solution, the preparation of the modified electrode material comprises the following steps:

[0023] S1.1. Clean the basic electrode material and remove surface impurities;

[0024] S1.2, adding the basic electrode material to a 2% (w / v) aqueous alcohol solution of an organosilicon compound containing an amine group, and ultrasonically dispersing for 30 minutes;

[0025] S1.3. Take out the silver nanowires and dry them at 60°C for 2 h to obtain modified silver nanowires.

[0026] On the other hand, the present invention provides a method for preparing the electrically debondable adhesive described above, comprising the following steps:

[0027] S2.1, weigh each component in proportion and add them into the mixer in sequence;

[0028] S2.2, firstly mix the acrylic polymer, conductive filler, plasticizer and antistatic agent evenly;

[0029] S2.3, then add curing agent and stir for 10-12 minutes;

[0030] S2.4, add modified electrode materials and additives, and stir for 14-16 minutes;

[0031] S2.5. After standing at room temperature for 24-26 hours, heat at 80-85°C for 2 hours to complete curing.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] In the electrically debondable adhesive and the preparation method thereof, butyl acrylate-ethyl acrylate copolymer is selected as the main component. This polymer has high bonding strength and good flexibility, can ensure the strong adhesion of the adhesive on a variety of substrates, and at the same time maintains a certain flexibility and ductility, and is suitable for use in occasions requiring flexibility, such as flexible electronic devices;

[0034] By introducing an organosilicon compound containing an amine group on the surface of a basic electrode material (such as silver nanowires, conductive fibers and metal foil) for modification, the conductivity of the electrode material is significantly improved. The modified electrode material can form weak interaction forces such as hydrogen bonds with the hydroxyl groups in the acrylic polymer, which enhances the compatibility and dispersibility between the electrode material and other components of the adhesive, thereby further improving the conductivity of the adhesive. When a voltage is applied, the electrode material can respond quickly, accelerate the redistribution of the internal charge of the adhesive, and promote the occurrence of the debonding process; through the introduction of the modified electrode material, the adhesive can respond quickly and achieve rapid debonding after applying a specific voltage. This feature is particularly important in the assembly and maintenance of electronic components, which can greatly reduce the cost and difficulty of disassembling and replacing components, while avoiding damage to the components, and improving the maintenance efficiency and reliability of electronic equipment; in addition, the modified electrode material has good weather resistance, can resist the influence of ultraviolet rays, moisture and other factors, and ensure that the performance of the adhesive is stable under different environmental conditions. This allows the adhesive of the present invention to maintain good bonding and conductivity after long-term use, extending the service life of the product.

[0035] The adhesive of the present invention is not only suitable for the assembly and maintenance of electronic components, but can also be applied to flexible electronic devices, smart wearable devices, automotive electronics and other fields to meet the needs of different application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1This is an overall flow chart of Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0038] Embodiment 1: This embodiment aims to provide an electrically debondable adhesive suitable for high temperature environments, comprising the following raw materials:

[0039] Acrylic acid ester polymer, using butyl acrylate-ethyl acrylate copolymer, the amount is 50 parts by weight;

[0040] Conductive filler, using a mixture of carbon nanotubes and conductive polymer (poly 3,4-ethylenedioxythiophene / polystyrene sulfonate), with an amount of 4 parts by weight;

[0041] Plasticizer, using dioctyl sebacate, the amount is 12 parts by weight;

[0042] Antistatic agent: polyether antistatic agent (polyoxyethylene ether) is used in an amount of 3 parts by weight;

[0043] Curing agent: epoxy resin curing agent (bisphenol A epoxy resin) is used in an amount of 5 parts by weight;

[0044] The modified electrode material is made of silver nanowires modified by an organosilicon compound containing an amine group (amino silicone oil), with an amount of 7 parts by weight;

[0045] The auxiliary agents include antioxidant 1010, ultraviolet absorber UV-326 and silane coupling agent, with the usage amount being 3 parts by weight.

[0046] according to Figure 1 As shown, the preparation method is as follows:

[0047] (1) Preparation of modified electrode materials:

[0048] The silver nanowires were cleaned to remove surface impurities; the silver nanowires were added to a 2% (w / v) hydroalcoholic solution of an organosilicon compound containing an amine group, and ultrasonically dispersed for 30 minutes to ensure that the modifier was evenly covered on the surface of the silver nanowires; finally, the silver nanowires were taken out and dried at 60°C for 2 hours to obtain the modified silver nanowires.

[0049] (2) Adhesive preparation:

[0050] Weigh each component in proportion and add them to the blender in sequence; first mix the acrylic polymer, conductive filler, plasticizer and antistatic agent evenly; then add the curing agent and stir for 10 minutes; finally add the modified electrode material and additives, stir for 15 minutes, let stand at room temperature for 24 hours, and then heat at 80°C for 2 hours to complete the curing.

[0051] In this embodiment, the amino group (-NH2) in the organosilicon compound containing amine groups chemically adsorbs with the oxide or hydroxyl group (-0H) on the surface of the silver nanowires to form a stable chemical bond, thereby improving the surface activity and dispersibility of the silver nanowires. Secondly, the amine group in the organosilicon compound containing amine groups forms a hydrogen bond with the hydroxyl group (-C00H) in the acrylic polymer, thereby enhancing the cohesion and adhesion of the adhesive; in addition, the bisphenol A epoxy resin reacts with the hydroxyl group (-0H) in the acrylic polymer to form a cross-linked network, thereby improving the mechanical properties and heat resistance of the adhesive.

[0052] Embodiment 2: This embodiment aims to provide an electrically debondable adhesive suitable for low temperature environments, comprising the following raw materials:

[0053] Acrylic acid ester polymer, using butyl acrylate-ethyl acrylate copolymer, the amount is 60 parts by weight;

[0054] Conductive filler, graphene, used in an amount of 5 parts by weight;

[0055] Plasticizer, using dioctyl sebacate, the amount is 8 parts by weight;

[0056] Antistatic agent: quaternary ammonium salt antistatic agent (stearyl trimethyl sodium chloride) is used in an amount of 4 parts by weight;

[0057] Curing agent: isocyanate curing agent (hexamethylene diisocyanate) is used in an amount of 3 parts by weight;

[0058] The modified electrode material is a conductive fiber modified by an organosilicon compound containing an amine group (amino silicone oil) in an amount of 10 parts by weight;

[0059] The auxiliary agents include antioxidant 1010, ultraviolet absorber UV-326 and silane coupling agent, with the usage amount being 3 parts by weight.

[0060] The preparation method is as follows:

[0061] (1) Preparation of modified electrode materials:

[0062] The conductive fiber was cleaned to remove surface impurities; the silver nanowires were added to a 2% (w / v) aqueous alcohol solution of an organosilicon compound containing an amine group, and ultrasonically dispersed for 30 minutes to ensure that the modifier was evenly covered on the surface of the silver nanowires; finally, the silver nanowires were taken out and dried at 60°C for 2 hours to obtain the modified conductive fiber;

[0063] (2) Adhesive preparation:

[0064] Same method as Example 1.

[0065] In this embodiment, the amino group (-NH2) in the organosilicon compound containing amine groups chemically adsorbs with the hydroxyl group (-0H) on the surface of the conductive fiber to form a stable chemical bond, thereby improving the surface activity and dispersibility of the silver nanowires. Secondly, the amine group in the organosilicon compound containing amine groups forms a hydrogen bond with the hydroxyl group (-C00H) in the acrylic polymer, thereby enhancing the cohesion and adhesion of the adhesive; in addition, hexamethylene diisocyanate reacts with the hydroxyl group (-0H) in the acrylic polymer to form a cross-linked network, thereby improving the mechanical properties and cold resistance of the adhesive.

[0066] Embodiment 3: This embodiment aims to provide an electrically debondable adhesive suitable for high-strength bonding, comprising the following raw materials:

[0067] Acrylic acid ester polymer, using butyl acrylate-ethyl acrylate copolymer, the amount is 58 parts by weight;

[0068] Conductive filler, using carbon nanotubes, the amount is 4 parts by weight;

[0069] Plasticizer: dioctyl phthalate, used in an amount of 10 parts by weight;

[0070] Antistatic agent: quaternary ammonium salt antistatic agent (stearyl trimethyl sodium chloride) is used in an amount of 3 parts by weight;

[0071] Curing agent: isocyanate curing agent (toluene diisocyanate) is used in an amount of 4 parts by weight;

[0072] The modified electrode material is a metal foil modified by an organosilicon compound containing an amine group (amino silicone oil) in an amount of 6 parts by weight;

[0073] The auxiliary agents include antioxidant 1010, ultraviolet absorber UV-326 and silane coupling agent, with the usage amount being 3 parts by weight.

[0074] The preparation method is as follows:

[0075] (1) Preparation of modified electrode materials:

[0076] The metal foil was cleaned to remove surface impurities; the silver nanowires were added to a 2% (w / v) aqueous alcohol solution of an organosilicon compound containing an amine group, and ultrasonically dispersed for 30 minutes to ensure that the modifier was evenly covered on the surface of the silver nanowires; finally, the silver nanowires were taken out and dried at 60°C for 2 hours to obtain a modified metal foil;

[0077] (2) Adhesive preparation:

[0078] Same method as Example 1.

[0079] In this embodiment, the amino group (-NH2) in the organosilicon compound containing amine groups chemically adsorbs with the oxide or hydroxyl group (-0H) on the surface of the metal foil to form a stable chemical bond, thereby improving the surface activity and dispersibility of the silver nanowires. Secondly, the amine group in the organosilicon compound containing amine groups forms a hydrogen bond with the hydroxyl group (-C00H) in the acrylic polymer, thereby enhancing the cohesion and adhesion of the adhesive; in addition, toluene diisocyanate reacts with the hydroxyl group (-0H) in the acrylic polymer to form a cross-linked network, thereby improving the mechanical properties and bonding strength of the adhesive.

[0080] Embodiment 4: This embodiment aims to provide an electrically debondable adhesive suitable for a moisture-proof environment, comprising the following raw materials:

[0081] Acrylic acid ester polymer, using butyl acrylate-ethyl acrylate copolymer, the amount is 52 parts by weight;

[0082] Conductive filler, using a mixture of carbon nanotubes and graphene, with an amount of 3 parts by weight;

[0083] Plasticizer, using dioctyl sebacate, the amount is 9 parts by weight;

[0084] Antistatic agent: polyether antistatic agent (polyoxyethylene ether) is used in an amount of 4 parts by weight;

[0085] Curing agent, using epoxy resin curing agent (bisphenol A epoxy resin), the amount is 4 parts by weight;

[0086] The modified electrode material is made of silver nanowires modified by an organosilicon compound containing an amine group (amino silicone oil), with an amount of 8 parts by weight;

[0087] The auxiliary agents include antioxidant 1010, ultraviolet absorber UV-326 and silane coupling agent, with the usage amount being 3 parts by weight.

[0088] The preparation method is as follows:

[0089] (1) Preparation of modified electrode materials:

[0090] Same as the method of Example 1;

[0091] (2) Adhesive preparation:

[0092] Same method as Example 1.

[0093] In this embodiment, the amino group (-NH2) in the organosilicon compound containing amine groups chemically adsorbs with the oxide or hydroxyl group (-0H) on the surface of the silver nanowires to form a stable chemical bond, thereby improving the surface activity and dispersibility of the silver nanowires. Secondly, the amine group in the organosilicon compound containing amine groups forms a hydrogen bond with the hydroxyl group (-C00H) in the acrylic polymer, thereby enhancing the cohesion and adhesion of the adhesive; in addition, the bisphenol A type epoxy resin reacts with the hydroxyl group (-0H) in the acrylic polymer to form a cross-linked network, thereby improving the mechanical properties and bonding strength of the adhesive.

[0094] Embodiment 5: This embodiment provides an electrically debondable adhesive suitable for quick release, comprising the following raw materials:

[0095] Acrylic acid ester polymer, using butyl acrylate-ethyl acrylate copolymer, the amount is 54 parts by weight;

[0096] Conductive filler, using a mixture of carbon nanotubes and graphene, with an amount of 4 parts by weight;

[0097] Plasticizer, using dioctyl sebacate, the amount is 11 parts by weight;

[0098] Antistatic agent: quaternary ammonium salt antistatic agent (stearyl trimethyl sodium chloride) is used in an amount of 3 parts by weight;

[0099] Curing agent: isocyanate curing agent (hexamethylene diisocyanate) is used in an amount of 4 parts by weight;

[0100] The modified electrode material is made of silver nanowires modified by an organosilicon compound containing an amine group (amino silicone oil), with an amount of 7 parts by weight;

[0101] The auxiliary agents include antioxidant 1010, ultraviolet absorber UV-326 and silane coupling agent, with the usage amount being 3 parts by weight.

[0102] The preparation method is as follows:

[0103] (1) Preparation of modified electrode materials:

[0104] Same as the method of Example 1;

[0105] (2) Adhesive preparation:

[0106] Same method as Example 1.

[0107] In this embodiment, the amino group (-NH2) in the organosilicon compound containing amine groups chemically adsorbs with the oxide or hydroxyl group (-0H) on the surface of the silver nanowires to form a stable chemical bond, thereby improving the surface activity and dispersibility of the silver nanowires. Secondly, the amine group in the organosilicon compound containing amine groups forms a hydrogen bond with the hydroxyl group (-C00H) in the acrylic polymer, thereby enhancing the cohesion and adhesion of the adhesive; in addition, hexamethylene diisocyanate reacts with the hydroxyl group (-0H) in the acrylic polymer to form a cross-linked network, thereby improving the mechanical properties and quick release performance of the adhesive.

[0108] Test Example 1: This test example aims to evaluate the performance of the electrically debondable adhesives provided in Examples 1-5.

[0109] Test method:

[0110] (1) Bond strength test: Use a tensile testing machine to measure the bond strength of adhesives on different substrates;

[0111] (2) Conductivity test: Use the four-probe method to measure the resistivity of the adhesive;

[0112] (3) Antistatic performance test: Use a surface resistance meter to measure the surface resistance of the adhesive;

[0113] (4) High temperature resistance test: The adhesive sample is placed at high temperature (150°C) for 24 hours to test the changes in its bonding strength and conductive properties;

[0114] (5) Low temperature resistance test: Place the adhesive sample at low temperature (-40°C) for 24 hours to test the changes in its bonding strength and conductive properties;

[0115] (6) Quick release performance test: After applying a certain voltage, measure the release time of the adhesive and the residual bonding strength after release.

[0116] Table 1 Performance of electrically debondable adhesive of Example 1

[0117] Table 2 Performance of electrically debondable adhesive of Example 2

[0118] Table 3 Performance of electrically debondable adhesive of Example 3

[0119] Table 4 Performance of electrically debondable adhesive of Example 4

[0120] Table 5 Performance of electrically debondable adhesive of Example 5

[0121] As shown in Tables 1 to 5, the bonding strength of the electrically debondable adhesives provided in all Examples 1 to 5 exceeds 5.5 MPa, indicating that the adhesives provided in this case have good bonding properties; the conductive properties are all between 0.04 and 0.08 Ω·cm, indicating that the adhesives have good conductive properties; the surface resistance is between 1.0×10^7 and 1.5×10^7, which meets the anti-static requirements; Examples 1 to 3 maintain good bonding strength and conductive properties at 150°C, and the surface is suitable for high temperature environments; Example 2 maintains good bonding strength and conductive properties at -40°C, and the surface is suitable for low temperature environments; Example 4 maintains good performance in high humidity environments, and the surface is suitable for moisture-proof environments.

[0122] In summary, the electrically debondable adhesive provided in this case exhibits excellent performance in the applicable environment, proving the effectiveness of the adhesive provided by the present invention in terms of bonding strength, conductive properties, antistatic properties, high and low temperature resistance, and quick detachment performance.

[0123] Comparative Example 1: This comparative example provides an adhesive that does not contain an acrylic polymer, including the following raw materials:

[0124] Polyurethane polymer, used in an amount of 55 parts by weight;

[0125] Conductive filler, using a mixture of carbon nanotubes and graphene, with an amount of 4 parts by weight;

[0126] Plasticizer, using dioctyl sebacate, the amount is 10 parts by weight;

[0127] Antistatic agent: quaternary ammonium salt antistatic agent (stearyl trimethyl sodium chloride) is used in an amount of 3 parts by weight;

[0128] Curing agent: isocyanate curing agent (hexamethylene diisocyanate) is used in an amount of 4 parts by weight;

[0129] The modified electrode material is made of silver nanowires modified by an organosilicon compound containing amine groups (amino silicone oil), with an amount of 8 parts by weight;

[0130] The auxiliary agents include antioxidant 1010, ultraviolet absorber UV-326 and silane coupling agent, with the usage amount being 3 parts by weight.

[0131] Comparative Example 2: This comparative example provides an adhesive that does not use modified electrode materials, including the following raw materials:

[0132] Acrylic acid ester polymer, using butyl acrylate-ethyl acrylate copolymer, the amount is 55 parts by weight;

[0133] Conductive filler, using a mixture of carbon nanotubes and graphene, with an amount of 4 parts by weight;

[0134] Plasticizer, using dioctyl sebacate, the amount is 10 parts by weight;

[0135] Antistatic agent: quaternary ammonium salt antistatic agent (stearyl trimethyl sodium chloride) is used in an amount of 3 parts by weight;

[0136] Curing agent: isocyanate curing agent (hexamethylene diisocyanate) is used in an amount of 4 parts by weight;

[0137] Unmodified electrode material, using silver nanowires, with an amount of 8 parts by weight;

[0138] The auxiliary agents include antioxidant 1010, ultraviolet absorber UV-326 and silane coupling agent, with the usage amount being 3 parts by weight.

[0139] Comparative Example 3: This comparative example provides an adhesive using other modified electrode materials, including the following raw materials:

[0140] Acrylic acid ester polymer, using butyl acrylate-ethyl acrylate copolymer, the amount is 55 parts by weight;

[0141] Conductive filler, using a mixture of carbon nanotubes and graphene, with an amount of 4 parts by weight;

[0142] Plasticizer, using dioctyl sebacate, the amount is 10 parts by weight;

[0143] Antistatic agent: quaternary ammonium salt antistatic agent (stearyl trimethyl sodium chloride) is used in an amount of 3 parts by weight;

[0144] Curing agent: isocyanate curing agent (hexamethylene diisocyanate) is used in an amount of 4 parts by weight;

[0145] The modified electrode material is 8 parts by weight of silver nanowires modified by polyacrylic acid;

[0146] The auxiliary agents include antioxidant 1010, ultraviolet absorber UV-326 and silane coupling agent, with the usage amount being 3 parts by weight.

[0147] Comparative Example 4: This comparative example provides an adhesive comprising the following raw materials:

[0148] Acrylic acid ester polymer, using butyl acrylate-ethyl acrylate copolymer, the amount is 45 parts by weight;

[0149] Conductive filler, using a mixture of carbon nanotubes and graphene, with an amount of 2 parts by weight;

[0150] Plasticizer, using dioctyl sebacate, the amount is 15 parts by weight;

[0151] Antistatic agent: quaternary ammonium salt antistatic agent (stearyl trimethyl sodium chloride) is used in an amount of 5 parts by weight;

[0152] Curing agent: isocyanate curing agent (hexamethylene diisocyanate) is used in an amount of 2 parts by weight;

[0153] The modified electrode material is made of silver nanowires modified by an organosilicon compound containing an amine group (amino silicone oil), with an amount of 12 parts by weight;

[0154] The auxiliary agents include antioxidant 1010, ultraviolet absorber UV-326 and silane coupling agent, with the usage amount being 4 parts by weight.

[0155] Comparative Example 5: This comparative example provides an adhesive that does not contain an antistatic agent, comprising the following raw materials:

[0156] Acrylic acid ester polymer, using butyl acrylate-ethyl acrylate copolymer, the amount is 55 parts by weight;

[0157] Conductive filler, using a mixture of carbon nanotubes and graphene, with an amount of 4 parts by weight;

[0158] Plasticizer, using dioctyl sebacate, the amount is 10 parts by weight;

[0159] Curing agent: isocyanate curing agent (hexamethylene diisocyanate) is used in an amount of 4 parts by weight;

[0160] The modified electrode material is made of silver nanowires modified by an organosilicon compound containing an amine group (amino silicone oil), with an amount of 8 parts by weight;

[0161] The auxiliary agents include antioxidant 1010, ultraviolet absorber UV-326 and silane coupling agent, with the usage amount being 3 parts by weight.

[0162] Test Example 2: The purpose of this test example is to compare the adhesives provided in Comparative Examples 1-5 with the adhesive provided in Example 1.

[0163] The test method adopts the test example method.

[0164] Table 6 Debonding adhesive properties of Example 1 and Comparative Examples 1-5

[0165] According to Table 6, it can be seen that the bonding strength of Comparative Example 1 which does not contain an acrylic polymer is significantly reduced (5.0 MPa), the conductivity is significantly reduced (0.10 Ω·cm), the surface resistance is significantly increased (2.5×10^7Ω), the bonding strength and conductivity at high temperature are significantly reduced (4.5 MPa, 0.12 Ω·cm), and the rapid detachment time is significantly increased (3.5 s), indicating that the acrylic polymer is a key component for improving the bonding strength, and helps to improve the conductivity, antistatic performance, high temperature resistance and rapid detachment performance;

[0166] In Comparative Example 2, which does not use the modified electrode material, the bonding strength of Comparative Example 2 is low (5.5 MPa), the conductivity is significantly reduced (0.10 Ω·cm), the surface resistance is significantly increased (2.5×10^7 Ω), the bonding strength and conductivity at high temperature are significantly reduced (4.5 MPa, 0.12 Ω·cm), and the fast detachment time is significantly increased (3.5 s), indicating that the modified electrode material provided by the present invention helps to improve the bonding performance, conductivity, antistatic performance, high temperature resistance and fast detachment performance;

[0167] Comparative Example 3 using other modified electrode materials has a slightly lower bonding strength (5.7MPa), slightly worse conductivity (0.08Ω·cm), slightly higher surface resistance (1.6×10^7Ω), slightly worse bonding strength and conductivity at high temperature (5.2MPa, 0.10Ω·cm), and slightly longer rapid detachment time (3.0s), indicating that the modification effect of the organosilicon compound containing amine groups is better;

[0168] Comparative Example 4, which is not within the raw material dosage range of the present invention, has a slightly lower bonding strength (5.3 MPa), slightly poorer conductivity (0.09 Ω·cm), slightly higher surface resistance (2.0×10^7 Ω), slightly poorer bonding strength and conductivity at high temperature (4.8 MPa, 0.11 Ω·cm), and a longer rapid detachment time (3.3 s), indicating that the ratio within the raw material dosage range is better;

[0169] Comparative Example 5, which does not contain an antistatic agent, has a slightly lower bonding strength (6.1 MPa), slightly worse conductivity (0.05 Ω·cm), and a slightly higher surface resistance (2.0×10^7 Ω). The bonding strength and conductivity at high temperature are slightly worse (5.7 MPa, 0.06 Ω·cm), and the quick detachment time is slightly longer (2.6 s). Except that the antistatic performance is greatly affected, there are no significant differences.

[0170] In summary, it can be seen that the electrically detachable adhesive provided by the present invention shows significant advantages in terms of bonding strength, electrical conductivity, antistatic performance, high temperature resistance and quick detachment performance, especially the optimization of the acrylic polymer, modified electrode material and raw material dosage range, which plays a key role in improving the comprehensive performance of the adhesive.

[0171] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. An electrically debondable adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: Acrylate polymer, 50-60 parts by weight; Conductive filler, 3-5 parts by weight; Plasticizer, 8-12 parts by weight; Antistatic agent, 2-4 parts by weight; Curing agent, 3-5 parts by weight; Modified electrode material, 5-10 parts by weight; Auxiliary agent, 2-4 parts by weight; The modified electrode material is prepared by modifying a basic electrode material with a modifier, and is used to increase the electrolysis speed of an electrically debondable adhesive, while interacting with an acrylic polymer to improve bonding performance.

2. The electrically debondable adhesive according to claim 1, characterized in that: The modifier is an organosilicon compound containing an amine group, the basic electrode material is one of silver nanowires, conductive fibers and metal foils; the organosilicon compound containing an amine group is one of amino silicone oil, amino-modified silicone coupling agent or amino-modified polysiloxane.

3. The electrically debondable adhesive according to claim 1, characterized in that: The acrylic acid ester polymer is a butyl acrylate-ethyl acrylate copolymer.

4. The electrically debondable adhesive according to claim 1, characterized in that: The conductive filler is at least one of carbon nanotubes, graphene and conductive polymers, and the conductive polymer is one of poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate, polypyrrole or polyaniline.

5. The electrically debondable adhesive according to claim 1, characterized in that: The plasticizer is one of dioctyl phthalate and dioctyl sebacate.

6. The electrically debondable adhesive according to claim 1, characterized in that: The curing agent is an isocyanate curing agent or an epoxy resin curing agent.

7. The electrically debondable adhesive according to claim 1, characterized in that: The antistatic agent is one of a quaternary ammonium salt antistatic agent or a polyether antistatic agent. The quaternary ammonium salt antistatic agent is stearyl trimethyl sodium chloride, and the polyether antistatic agent is polyoxyethylene ether.

8. The electrically debondable adhesive according to claim 1, characterized in that: The auxiliary agent comprises an antioxidant, an ultraviolet absorber and a coupling agent. The antioxidant is antioxidant 1010, the ultraviolet absorber is UV-326, and the coupling agent is a silane coupling agent.

9. The electrically debondable adhesive according to claim 2, characterized in that: The preparation of the modified electrode material comprises the following steps: S1.

1. Clean the basic electrode material and remove surface impurities; S1.2, adding the basic electrode material to a 2% (w / v) aqueous alcohol solution of an organosilicon compound containing an amine group, and ultrasonically dispersing for 30 minutes; S1.

3. Take out the silver nanowires and dry them at 60°C for 2 h to obtain modified silver nanowires.

10. A method for preparing the electrically debondable adhesive as claimed in claim 1, characterized in that: The following steps are involved: S2.

1. Weigh each component in proportion and add them into the mixer in sequence; S2.2, firstly mix the acrylic polymer, conductive filler, plasticizer and antistatic agent evenly; S2.3, then add curing agent and stir for 10-12 minutes; S2.4, add modified electrode materials and additives, and stir for 14-16 minutes; S2.

5. After standing at room temperature for 24-26 hours, heat at 80-85°C for 2 hours to complete curing.

Citation Information

Cited By

  • Electrically peelable adhesive composition

    CN120843023A

  • An electrically peelable adhesive composition

    CN120843023B

  • Device capable of stain-free debonding on demand

    WO2026099181A1